Estrutura molecular e citogenética de cromossomos B em Astyanax paranae (Characiformes, Characidae) - Silva, Duílio Mazzoni Zerbinato de Andrade [UNESP] (2014)
In addition to the standard complement of chromosomes A, some organisms have extra genomic elements called chromosomes B. These cryptic elements are present in approximately 15% of eukaryotic species. The molecular mechanisms that govern the evolution of these segments may involve gene silencing, heterocromatinization, accumulation of repetitive DNA and transposons. The present study was inserted in the general studies program of cytogenetics and molecular genetics of Neotropical fishes in development at the Laboratory of Biology and Genetics of Fishes (IBB/UNESP/Botucatu, SP) and aimed to study the molecular structure of B chromosomes and cytogenetics of Astyanax paranae. Classical and molecular cytogenetic analyzes were performed on specimens of this species from the Capivara River, Tietê River Basin (Botucatu-SP), revealing a pattern diploid number of this species of 2n=50 chromosomes, with the karyotype formula identified by 8m+12sm+14st+16a and FN=84. Furthermore, supernumerary chromosomes found in the cells of thirteen samples (12 females and 1 male), and may appear in two variants, one metacentric (Bm) and a submetacentric (Bsm). The C-banding showed blocks of constitutive heterochromatin mainly in the terminal region of the long arm of the first five pairs of acrocentric chromosomes and in the B chromosome. The 18S rDNA mapping showed sites on some chromosomes, and ...